Profile of Acute Coronary Syndrome In Young People: A Hospital Based Observational Study in Western Nepal - Paudel, Navaraj; Alurkar, Vijay Madhab; Jha, Girija Shankar; Kafle, Ramchandra; Sapkota, Subash; Lamsal, Lekhnath (Birat Journal of Health Sciences, 2018)
Introduction: Acute coronary syndrome is associated with high mortality and morbidity. The incidence of acute coronary events in young is increasing. Objectives: This study aimed at evaluating the profile of acute coronary syndrome in young people in the western part of Nepal. Methodology: A retrospective study was designed. All patients admitted for acute coronary syndromes were taken and data of acute coronary syndrome involving patients aged less than 45 years from April 2015 through December 2017 were collected in a pre-structured proforma and analyzed. Results: There were 712 (489 males and 223 females with M:F=2.19:1) acute coronary syndrome patients admitted during the study period. Only 79 (12.9%) patients were patients <45 years of age. Commonest risk factor of acute coronary syndrome was smoking (69%) followed by dyslipidemia (46.8%), hypertension (45.5%) and diabetes (14%). Out of 79 patients of young acute coronary syndrome, 37 (46.8%) presented with ST elevated myocardial infarction, 16 (20.2%) with non-ST elevated myocardial infarction and 26 (32.9%) with unstable angina. Most common finding in coronary angiography was single vessel disease (35%) –left anterior descending artery being the commonest (53% of single vessel disease), double vessel disease (17.7%), non-critical coronary artery disease (16.4%), triple vessel disease (7.6%) and left main (1.2%). Myocardial bridging was seen in 1.2% and 20% had normal coronaries. Comparison of males and females in different categories of acute coronary showed that males predominate significantly in ST elevated myocardial infarction (odds ratio: 2.99; p=0.03) but there was no significant difference between the males and females presenting either with Non ST elevated myocardial infarction or unstable angina. Conclusion: Acute coronary syndrome in young people was common (12.9%) particularly males with Non ST elevated myocardial infarction. Smoking was the commonest risk factor. Public awareness regarding stoppage of cigarette smoking should be focused to prevent such events especially in the young population. BJHS 2018;3(1)5 : 361-365